Tetrandrine Inhibits Titanium Particle-Induced Inflammatory Osteolysis through the Nuclear Factor-κB Pathway - Zige Liu; Yan Li; Fengying Guo; Chen Zhang; Guorui Song; Jiahao Yang; Desheng Chen (Hindawi Limited, 2020)
Peri-implant osteolysis (PIO) and the subsequent aseptic loosening are the main reasons for artificial joint implant failure. Existing methods for treating aseptic loosening are far from satisfactory, necessitating advanced drug exploration. This study is aimed at investigating the effect and underlying mechanism of tetrandrine (Tet) on inflammatory osteolysis. We established a Ti particle-induced inflammatory osteolysis mouse model and administered Tet or an equal volume of phosphate-buffered saline (PBS). Two weeks later, specimens were collected. Histological staining showed that Tet administration inhibited Ti-stimulated osteolysis. Tartrate-resistant acid phosphate (TRAP) staining and transmission electron microscopy (TEM) demonstrated that osteoclast formation was remarkably inhibited in the groups treated with Tet in a dose-dependent manner. In addition, relevant inflammatory cytokines (tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6) were also significantly reduced in the calvaria of the Tet-treated groups. Exposure of receptor activator for nuclear factor-κB ligand- (RANKL-) induced bone marrow-derived macrophages (BMMs) and RAW264.7 cells to Tet significantly reduced osteoclast formation, F-actin ring formation, bone resorption, and the expression of relevant genes (matrix metallopeptidase 9 (MMP-9), TRAP, and nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1)) during osteoclastogenesis in vitro. Mechanistic studies using Western blotting demonstrated that Tet inhibited the nuclear factor (NF)-κB signaling pathway by decreasing the phosphorylation of inhibitor of NF-κB α (IκBα) and p65, which play important roles in osteoclast formation. Collectively, our data indicate that Tet suppressed Ti-induced inflammatory osteolysis and osteoclast formation in mice, suggesting that Tet has the potential to be developed to treat and prevent wear particle-induced inflammatory osteolysis.